Penile Anomalies in Adolescence - Dan Wood; Christopher Woodhouse (The Scientific World Journal)
This article considers the impact and outcomes of both treatment and underlying condition of penile anomalies in adolescent males. Major congenital anomalies (such as exstrophy/epispadias) are discussed, including the psychological outcomes, common problems (such as corporal asymmetry, chordee, and scarring) in this group, and surgical assessment for potential surgical candidates. The emergence of new surgical techniques continues to improve outcomes and potentially raises patient expectations. The importance of balanced discussion in conditions such as micropenis, including multidisciplinary support for patients, is important in order to achieve appropriate treatment decisions. Topical treatments may be of value, but in extreme cases, phalloplasty is a valuable option for patients to consider. In buried penis, the importance of careful assessment and, for the majority, a delay in surgery until puberty has completed is emphasised. In hypospadias patients, the variety of surgical procedures has complicated assessment of outcomes. It appears that true surgical success may be difficult to measure as many men who have had earlier operations are not reassessed in either puberty or adult life. There is also a brief discussion of acquired penile anomalies, including causation and treatment of lymphoedema, penile fracture/trauma, and priapism.